O menor infrator, a questão da maioridade penal e as medidas socioeducativas em prática no Brasil e no Amazonas - (:unkn) unknown (Universidade Federal do Amazonas, 2016)
This study aims to propose a discussion about the transformation of the state of social welfare to the penal state, we also developed the idea of people mass incarceration and criminalization of poverty as the way adopted for the solution of social problems and security. Secondly we discuss the issue of criminal responsibility and the consequences, also considering the importance of the media in this context and in the formation of collective thought. We also seek to conduct a brief history of the treatment for young people in conflict with the law, seeking to demonstrate the evolution of the legal processes and institutions to support juvenile offenders. Finally, the dissertation analyzes the implementation of educational measures and the reality of the application of penalties , the role of each organ and sphere of power, while scoring the need for integration of all and direct participation.
Keywords: Medidas socioeducativas; Maioridade penal; Ressocialização; CIÊNCIAS HUMANAS: SOCIOLOGIA